Desiminasi Ilmu Tentang Diabetes Mellitus Dan Pelatihan Senam Kaki Diabetik Sebagai Upaya Pencegahan Komplikasi Diabetes Mellitus Di Desa Kumbang Indah - Herlitawati Herlitawati; Devi Susanti; Taufik Hidayat; Yusnaini Yusnaini (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Diabetes mellitus (DM) is a long-term condition that requires lifelong treatment. The aim of this knowledge dissemination activity is to increase general knowledge about DM disease and increase awareness of the importance of doing diabetic foot exercises regularly to reduce blood sugar levels. We act as instructors or resource persons during demonstrations of diabetic foot exercise procedures. Additionally, ten third semester students helped us organize the event. The series of activities began with an introduction, explanation of the aims and objectives of DM, and distribution of DM material. After the material is complete, the location is set for a demonstration of diabetic foot exercises. Participants sit in chairs that have been prepared in advance. It can be seen that they are all very interested in following every instruction and movement shown by the counselor. Evaluation begins after all documents are submitted. Objective evaluation is by asking again about the sequence of leg exercise movements that have just been learned, while subjective evaluation is by asking how the participant feels after the activity. The result of this health education activity is that the public understands diabetes mellitus better and is more aware of the importance of diabetic foot exercises